Determinant Factors of Child Development in Various Ecosystem Zones in Papua - Manongga, Stefanus P.; Litik, Sherlie (International Journal Labs, 2023)
Background: The negative impact of malnutrition is generally associated with impaired motor development, behavioural and cognitive development which results in decreased learning achievement and social skills. Aim: The purpose of this study was to examine the situation of child development and to assess the role of various factors related to the development of children under five years of age in various ecosystem zones in Papua Province. Method: The research was carried out in four districts in Papua representing three ecosystem zones, namely the mainland coast, the middle plains and the mountains. Data was collected through structured interviews, observations and field measurements. Analysis of the differences in variables between ecosystem zones used the smallest significant difference test and the Kruskal Wallis test. Meanwhile, the analysis of the impact of malnutrition on children's development used Structural Equation Modelling-Regression with a partial least square approach using the SmartPLS version 3.2.9 application. Findings: The prevalence of Papuan children suffering from developmental delays reached 77.7%, especially in language development, fine motor adaptive, and personal social. An increase in the degree of malnutrition in the form of stunting suppresses the development of children to be low, while an increase in the degree of sickness in children has the potential to worsen the degree of malnutrition by suppressing the nutritional intake of children to be low.